Circ_0110940 Exerts an Antiapoptotic and Pro-Proliferative Effect in Gastric Cancer Cells via the miR-1178-3p/SLC38A6 Axis. (30th June 2022) - Miao, Xiaonan; Zou, Haiou; Pan, Lijuan; Cheng, Jing; Wu, Youshan; Chen, Rui; Su, Yong; Du, Hongwei
Abstract : Circular RNAs (circRNAs) are essential regulators in human cancers, including gastric cancer, by the miRNA/mRNA axis. A previous study identified the upregulation of circ_0110940 in human gastric cancer tissues. The present study performed in vitro assays to reveal the functions of circ_0110940 and its downstream miRNA/mRNA axis in gastric cancer cells. Traditional proliferation and apoptosis assays including colony formation, EdU staining, and Annexin V-PI staining assays were conducted. A luciferase reporter assay was performed to assess the binding between miR-1178-3p and circ_0110940 or SLC38A. We found the significant upregulation of circ_0110940 in human gastric cancer cells AGS and MKN45. Circ_0110940 was a stable circRNA and exerted an antiproliferative and proapoptotic effect in AGS and MKN45. Circ_0110940 binded with miR-1178-3p, which further targeted SLC38A6 3′UTR. Circ_0110940 degraded miR-1178-3p, and miR-1178-3p degraded SLC38A6. Thus, circ_0110940 has a positive effect on SLC38A6 expression. Furthermore, SLC38A6 rescued the effects of circ_0110940 knockdown on gastric cancer cell proliferation and apoptosis. In conclusion, circ_0110940 exerted an antiapoptotic and pro-proliferative effect in gastric cancer cells via the miR-1178-3p/SLC38A6 axis, which may provide basis for the targeted therapy of gastric cancer.